This preview shows page 1. Sign up to view the full content.
Unformatted text preview: N (2) = N (0) + 3 N (1) + 3 N (2) = 1 + 3(1) + 3(3) = 13 . We also nd for N (4) that N (4) = 3 j =0 4 j N ( j ) = 4 N (0) + 4 1 N (1) + 4 2 N (2) + 4 3 N (3) = N (0) + 4 N (1) + 3 4 2 N (2) + 4 N (3) = 1 + 4(1) + 6(3) + 4(13) = 75 . Problem 17 (why the binomial equals the multinomial) The expression n r is the number of ways to choose r objects from n , leaving another group of nr objects. The expression n r, nr is the number of divisions of n distinct...
View
Full
Document
 Winter '08
 G.JOGESHBABU
 Probability

Click to edit the document details